Traffict Density Affects Stomatal Character of Tanjung Plant (Mimusops elengi, L.) in Mataram City - Baiq Wiwik Purnama Sari; Prapti Sedijani; I Gde Mertha (Jurnal Biologi Tropis, 2021)
Increase in traffic density increases air pollution. Air pollution affects plant life physiologically, for the long run it could be morfologically, one of whichs is the stomatal characters. This research aimed to determine the influence of traffic density difference to the stomatal characteristic of Tanjung leaves (Mimusops elengi L.) in Mataram City. Sampling was carried out on 4 designated locations including the Unram Library (control) that has no traffic density, Jl. Dr. Sudjono (Low traffic), Jl. Ahmad Yani and Jl. Majapahit (high traffic). The method used was Post ex Facto, Purposive sampling. The measured parameters included the number of stomata, the number of open and closed stomata, the stomatal index, the stomatal size and the aperture size of the stomata. The research data was analyzed in a qualitative description and in a quantitative description using analysis of Varian (ANOVA). The results showed that the traffic density reduces the number of stamata as well as their size, the number of opended and increased the number of closed stomata, increases stomatal index due to stomatal damage and reduces stomatal aperture in Mataram city. It is concluded that traffic density affects stomatal haracter tanjung plant. Thrence, this finding reveals that stomatal character of tnajnjung plant can be used as air pollution bioindicator.